The characteristics of social maturity in infants and children with cochlear implants in China. (April 2020) - Li, Bei; Han, Kun; Yang, Lu; Huang, Meiping; Huang, Zhiwu; Li, Yun; Wu, Hao
Abstract: Objective: The primary aim of the current study was to examine the social maturity of infants and children with cochlear implants in China. A secondary aim was to document the associated information using a General Condition Questionnaire for further cohort study in this population. Materials and methods: This is a retrospective cross-sectional observational study and a pilot study. Between July and December 2017, data from all implantees between the ages of 6 months and 14 years who presented to the Hearing and Speech Center of Shanghai Ninth People's Hospital for mapping were collected. There were 119 non-overlapping cases in total. Data were collected via the Infants-Junior Middle School Students' Social-Life Abilities Scale (S-M scale) and a structured General Condition Questionnaire. The S-M scale was used for social adaptability measurement for children aged between 6 months to 14 yearsold. The General Condition Questionnaire, which was completed by the parents or primary caregivers of the implantees, gathered 3 aspects of personal information: the patient's history of hearing loss, personal history of rehabilitation and their past medical history. Results: Results showed that in 119 cases, 89 implantees (74.8%) were at or above a normal social maturity level. Thirty implantees (25.2%) scored lower than normal on the S-M standard score. Spearman's rank correlation indicated that the age at which hearing loss was noticed, the age of initial rehabilitation and the age at implantation were significantly correlated with the patients' scores on the S-M scale. Conclusion: In summary, most of the cochlear implantees showed normal social maturity, with the exception of 25.2% of implantees who performed at a lower level than their normal hearing peers. These findings suggest potential targets to investigate in future cohort studies in cochlear implantees.